Penelitian Sumber Daya Manusia (SDM) di Kabupaten Sukoharjo - Djiwandi Djiwandi; Retno Setyowati; Marcelinus Molo (Universitas Sebelas Maret, 2004)
This research aim to know the quality of peoples as human resources in Sukoharjo District. Peoples with high quality will be able to improve economic growth through goods and service production. Quality of humas resources can be improved, for example, increasing of education, health, and security.This research use secondary data from some source, including from Sukoharjo Dalam Angka. Reserach indicates that peoples of Sukoharjo District in the year 2003 is counted 808.810 head, level growth of peoples less 0,79%, women peoples 409.521 head, men 399.290 head, sex ratio 97,50.Education level show improvement from year to year, education mount master and diploma level. Health medium are quality a lot there are 6 public hospitals, 21 puskesmas, 47 ministrant puskesmas, 36 house copy privat sector, 199 doctor practice privat sector, 49 people dentist practice, 48 dispensary, the despitefully in district region there is 1.026 Posyandu, condition of security in Sukoharjo District is peaceful, downhill badness number from year to year. Pursuant to education, health, and security level, like above, human resources in Sukoharjo District are good.